Empathic brain responses in insula are modulated by levels of alexithymia but not autism - Bird, Geoffrey (Oxford University Press, 2010)
Difficulties in social cognition are well recognized in individuals with autism spectrum conditions (henceforth ‘autism’). Here we focus on one crucial aspect of social cognition: the ability to empathize with the feelings of another. In contrast to theory of mind, a capacity that has often been observed to be impaired in individuals with autism, much less is known about the capacity of individuals with autism for affect sharing. Based on previous data suggesting that empathy deficits in autism are a function of interoceptive deficits related to alexithymia, we aimed to investigate empathic brain responses in autistic and control participants with high and low degrees of alexithymia. Using functional magnetic resonance imaging, we measured empathic brain responses with an ‘empathy for pain’ paradigm assessing empathic brain responses in a real-life social setting that does not rely on attention to, or recognition of, facial affect cues. Confirming previous findings, empathic brain responses to the suffering of others were associated with increased activation in left anterior insula and the strength of this signal was predictive of the degree of alexithymia in both autistic and control groups but did not vary as a function of group. Importantly, there was no difference in the degree of empathy between autistic and control groups after accounting for alexithymia. These findings suggest that empathy deficits observed in autism may be due to the large comorbidity between alexithymic traits and autism, rather than representing a necessary feature of the social impairments in autism.